THE EFFECT OF PRODUCT QUALITY AND PRICE ON PURCHASE DECISIONS - Himami Firdausi; Nur Iftah Maufida (IZZI: Jurnal Ekonomi Islam, 2025)
The aim of this research is to evaluate how product quality and price influence the purchasing decisions made by female students at the Pesantren Al‑Mashduqiah Girls’ Store when choosing to buy the product. This study was conducted using a quantitative approach by distributing questionnaires to 38 participants. The results show that product quality and price have a positive and significant impact on purchasing decisions. High-quality products increase customer trust, while stable and affordable prices reduce perceived risk and encourage customer loyalty. Both factors jointly influence purchasing decisions in the boarding-school environment.